Valvular Excrescences: A Possible Transient Phenomenon - Peter Marstrand; Maiken Brit Jensen; Nikolaj Ihlemann (Case Reports in Cardiology)
The thrombogenic potential of Lambl excrescences (LE) is minimal unlike the benign tumour fibroelastoma wherefrom thrombi often originate. We present a patient with multiple strokes within a six-year period. A possible locus on the aortic valve was found and diagnosed as fibroelastoma. Before aortic valve substitution prior finding could not be visualized and surgery was aborted. Due to review of earlier Transesophageal Echocardiography (TEE) and the transient component, LE was accepted as the most plausible diagnosis. This illustrates the need for TEE just before surgery.